The synchronization of European credit cycles - Barbara Meller; Norbert Metiu (Deutsche Bundesbank, 2015)
We study the synchronization of credit booms and busts among 12 major European economies and the United States between 1972-2011. We propose a regression-based procedure to test whether boom-bust phases of credit cycles coincide across countries and to cluster countries with positively synchronized credit cycles. We find strong evidence against the existence of a common credit cycle across all countries. Instead, the credit cycles of Austria, Belgium, Germany, Ireland, and the Netherlands are clustered together, while Denmark, Finland, France, Italy, Spain, Sweden, the UK, and the US belong to another distinct cluster. Overall, the relationship among credit cycles is found to be stable over time. However, within each of the two clusters, credit cycles have been converging at least since the last decade. Using a simultaneous equations model, we find that deeper financial integration and a higher degree of business cycle co-movement are associated with stronger credit cycle synchronization.
Keywords: C32; F34; G15; 330; Business cycles; Credit booms; Financial cycles; Financial integration; Synchronization